The influence of intraoral devices in competitive anxiety levels of golf athletes – a pilot study - Cebola, Pedro (2022)
Communication abstract: Joint 3rd International Congresses of CiiEM “Research & Innovation in Human and Health Sciences” and the “UNESCO Chair for Teaching & Research in Digital Anatomy Paris Descartes, 2018”, held at Egas Moniz’ University Campus in Monte de Caparica, Almada, from 20-22 of June 2018.